Partial SAA patients benefit from delayed response of IST - Wang, Ting; Wang, Chaomeng; Liu, Chunyan; Shao, Zonghong; Fu, Rong (Frontiers in Immunology, 2023)
Introduction Severe aplastic anemia(SAA)is a severe disease characterized by immune-mediated bone marrow failure and pancytopenia. Immunosuppressive therapy (ATG plus CsA, IST) is the standard treatment for patients who are not suitable for allogeneic hematopoietic stem cell transplantation (allo-HSCT). Some patients have a delayed response after 6 months of ATG, and unnecessary to be given secondary ATG or allo-HSCT. We attempted to distinguish patients who may get potential delayed response from those who were really not responsive to IST. Methods We collected data from 45 SAA patients who were assessed no-response to IST at 6 months after rATG and failed to receive secondary ATG or allo-HSCT. Results CsA plus eltrombopag (EPAG) group has an extra 75% response rate while CsA maintenance group has an extra 44% response rate at 12 months. ATG was applied within 30 days after diagnosis, ATG dosage was suffificient (ATG/lymphocyte ≥2), and absolute reticulocyte count (ARC) was ≥30×109 /L at 6 months, indicated patients could get delayed response and benefifit from CsA maintenance. Addition of EPAG could give an even better response. Otherwise, secondary ATG or allo-HSCT treatment were recommended to be given immediately. Clinical Trial Registration https://www.chictr.org.cn/searchproj.aspx, identifier ChiCTR2300067615.